2004
DOI: 10.6090/jarq.38.259
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Isoflavones and Consumption of Oligosaccharides during Lactic Acid Fermentation of Soybean Milk

Abstract: Aiming to select suitable strains of lactic acid bacteria for producing yogurt-like functional food from soybean milk, the fermentation properties of 14 lactic acid bacterial strains belonging to genera Bifidobacterium, Lactobacillus, Lactococcus and Streptococcus were evaluated using soybean milk as the culture medium. All 14 strains examined were able to grow in soybean milk. Twelve out of the 14 strains lowered the pH of the medium and produced lactic acid. Tested strains showed a variety of consumption pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In 2003, Wang et al [13] reported that in similar situations, B. infantis CCRC 14633 takes about 40 hours and 48 hours of fermentation to reach pH 5.04 and pH 4.61, respectively. Bifi dobacterium breve JCM 1192 strain was reported to achieve a better fermentation profi le (drop in pH from 6.2 to 5.1 after 16 h), while B. adolescentis JCM 1275 and B. bifi dum JCM 1255 produced less acid during fermentation of soymilk [15]. Our results are comparable to some profi les produced by lactic acid bacteria such as Lactobacillus delbrueckii subsp.…”
Section: Changes In Titratable Acidity and Phsupporting
confidence: 76%
See 2 more Smart Citations
“…In 2003, Wang et al [13] reported that in similar situations, B. infantis CCRC 14633 takes about 40 hours and 48 hours of fermentation to reach pH 5.04 and pH 4.61, respectively. Bifi dobacterium breve JCM 1192 strain was reported to achieve a better fermentation profi le (drop in pH from 6.2 to 5.1 after 16 h), while B. adolescentis JCM 1275 and B. bifi dum JCM 1255 produced less acid during fermentation of soymilk [15]. Our results are comparable to some profi les produced by lactic acid bacteria such as Lactobacillus delbrueckii subsp.…”
Section: Changes In Titratable Acidity and Phsupporting
confidence: 76%
“…Moreover, some strains of this genus were also reported to be capable of metabolising α-galactosyl type galacto-oligosaccharides [25,26], thus soymilk that contains sucrose, raffi nose, stachyose, proteins, vitamins, etc., should be a good medium for growing bifi dobacteria [25]. This hypothesis was also proved by Bordignon et al [15] when they reported that B. bifi dum JCM 1255, B. breve JCM 1922 and B. infantis JCM 1222 strains preferentially fermented galacto-oligosaccharides rather than sucrose, during fermentation of soymilk. Although, due to α-galactosidase activity, Bifidobacteria are able to cleave α-galactosidic bonds, very few data are available in the literature related to properties of the α-galactosidase enzyme from this micro-organism.…”
Section: Acta Microbiologica Et Immunologicamentioning
confidence: 52%
See 1 more Smart Citation
“…(2002) found that when Bifidobacterium animalis Bb‐12 is grown in soymilk, hydrolysis of glucoside isoflavones increases aglycones from 8 to 50% of the total isoflavones. Bordignon et al. (2004) also showed that Bifidobacterium breve , Bifidobacterium bifidum and Lactobacillus casei subsp.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that probiotic organisms including Bifidobacterium, Lactobacillus acidophilus and L. casei increased the concentration of bioactive isoflavone aglycones in soymilk during fermentation. It has been reported that many bifidobacteria and some other lactic acids (Bordignon et al, 2004;Pyo et al, 2005;Chien et al, 2006) hydrolyse isoflavone glycosides into corresponding aglycones.…”
Section: Introductionmentioning
confidence: 99%